Primary health care strengthening through the lens of healthcare system thinking - Ramprakash Kaswa; Klaus von Pressentin (South African Family Practice)
Despite the strides made in healthcare, many countries still struggle to meet citizen healthcare needs, leading to global and regional health inequalities. The complex interactions between healthcare systems and disciplines present challenges for primary care providers and family physicians. Primary care providers must be equipped with tools and resources to effectively fulfil their duties, such as clinical governance, leadership and capacity building. This article focusses on various thinking approaches that primary care providers can employ, namely systems thinking, complexity science thinking and learning health systems thinking. We appreciate that individual styles and preferences, organisational culture and systemic realities influence multiple modes of thinking and decision-making. A range of modes of thinking and mental models will assist with tackling challenges and opportunities in the primary healthcare system. We hope this brief overview encourages readers to experiment with different ways of thinking to help facilitate innovative solutions.